Determination of Pyrethroids in Dendrobium officinale by Ultrasound/Microwave-Assisted Solid–Liquid–Solid Dispersive Extraction, Gas Chromatography, and Triple-Quadrupole Mass Spectrometry. (11th February 2017) - Wu, Huizhen; Qian, Mingrong; Wang, Jianmei; Zhang, Hu; Li, Zuguang
ABSTRACT: An ultrasound/microwave-assisted solid–liquid–solid dispersive extraction method was developed for the determination of 16 pyrethroid insecticides in Dendrobium officinale . The extraction and purification were performed in one step. The pyrethroids were extracted with 8:2 acetone:hexane and purified with a mixture of primary secondary amine, Florisil, C18, and graphitized carbon black. The extraction temperature, extraction time, and ultrasound power were optimized. Trans-cyfluthrin- d 6 was used as the internal standard to improve the accuracy. Under the optimized conditions, the recoveries of the pyrethroids were from 72.2 to 113.9% with the limits of detection between 0.29 and 9.38 µg kg −1 . The optimized method was successfully used for the determination of pyrethroids in commercial D. officinale samples and may allow monitoring pyrethroids in herbal products.